Penggunaan Model Pengajaran Terarah Dalam Meningkatkan Prestasi Dan Pemahaman Pelajaran IPS Pada Siswa Kelas VIII J SMP Negeri 1 Watampone Kabupaten Bone - kasma kasma (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2019)
The problems that need to be studied in this study are: (a) How is the improvement of social studies learning achievement by the application of directed teaching models (b) How the influence of the instructional model directed towards motivation to learn. The objectives of this study were: (a) to know the improvement in social studies learning achievements after the active learning method was applied to the directed learning model. (b) want to know the effect of social studies learning motivation after the active learning model directed learning model has been applied. This study uses action research as many as three cycles. Each cycle consists of four stages, namely: planning, implementing, observing, and reflecting. The subjects of this study were students of Class VIII J SMP Negeri 1 Watampone Kab. Bone. Data obtained in the form of formative test results, observation sheets of teaching and learning activities. Learning with active learning methods directed learning model has a positive impact in improving students' learning achievement which is characterized by increasing student mastery learning in each cycle, namely cycle I (20.00%), cycle II (95.00%). The application of the active learning model of the directed teaching model has a positive influence, which can increase the motivation of student learning as indicated by the average student response stating that students are interested and interested in being motivated to learn.